2009
DOI: 10.1134/s0006297909090041
|View full text |Cite
|
Sign up to set email alerts
|

Structural-functional characteristics of a new bioregulator isolated from bovine pigmented epithelium tissue

Abstract: A new bioregulator operating in ultralow doses corresponding to 10(-17) mg/ml has been isolated from tissue of pigmented epithelium of bovine eyes. It has been established that the functional basis of this bioregulator is a complex of a low molecular weight regulatory peptide (4372 Da) and a modulator consisting of a mixture of proteins with molecular weights of 14.980-66.283 kDa. It has been shown that the regulatory peptide is responsible for membranotropic activity of the bioregulator, and the modulator pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…It was demonstrated that the pigmented cells under cultiva tion conditions form large clusters localized in the cortical layer and perivascular spaces (hematopoiesis areas) and are present in the liver parenchyma. For this reason, we evaluated the activation of the pigmented cells in this model by their clusters area on histological sections of organ cultures in different experimental series [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that the pigmented cells under cultiva tion conditions form large clusters localized in the cortical layer and perivascular spaces (hematopoiesis areas) and are present in the liver parenchyma. For this reason, we evaluated the activation of the pigmented cells in this model by their clusters area on histological sections of organ cultures in different experimental series [10].…”
Section: Resultsmentioning
confidence: 99%
“…Maltsev from the Nesmeyanov Institute of Ele mentorganic Compounds, RAS (the method of the isolation and purification [10] was similar to the technique described above for the object studied in this work), and the pharmacological preparation Essen tiale forte (Aventis/Nattermann A. and Cie. GmbH, Germany) from the Russian pharmacy network. The vials were sealed under sterile conditions, placed on a RM5 roller (Assistant, Germany), and incubated for 72 h at 20-22°C and 35 rpm.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…At the same time, successive instillation of these bioregulators had the most pronounced effect on wound healing. Such a difference in the biological action of two bioregulators (each of them stimulated wound healing in the cornea in individual application) can be explained by changes in nanosized state of bioregulators in the solution caused by their interaction [11]. It has been previously shown that activity of bioregulators of this group was determined by their nanosize condition in solutions [11].…”
Section: Resultsmentioning
confidence: 99%
“…Bioregulators of this group are localized extracellularly, have a complex structure, and contain proteins, carbohydrates, and lipids [6]. Their activity is determined by the protein component [11]. Bioregulators of this group modulate adhesion, migration, differentiation, and cell proliferation in the original tissues.…”
mentioning
confidence: 99%
“…It was established that animal MHTB are peptide protein complexes with extracellu lar localization. MHB activity is determined by small peptides with molecular weights of 1000-6000 Da that bind with proteins modulating their biological effects [4][5][6][7]. The distinctive properties of MHTB include activity in very low doses (VLD), tissue but not species specificity, and the ability to stimulate the recovery and repair processes in injured or pathologically changed tissues due to the additional activation of cell regenera tion sources [3,8].…”
Section: Introductionmentioning
confidence: 99%